Integrins Cooperate With the EGFR/Ras Pathway to Preserve Epithelia Survival and Architecture in Development and Oncogenesis - Valencia-Expósito, Andrea; Gómez-Lamarca, M. Jesús; Widmann, Thomas J.; Martín-Bermudo, María D. (Frontiers in Cell and Developmental Biology, 2022)
Adhesion to the extracellular matrix (ECM) is required for normal epithelial cell survival. Disruption of this interaction leads to a specific type of apoptosis known as anoikis. Yet, there are physiological and pathological situations in which cells not connected to the ECM are protected from anoikis, such as during cell migration or metastasis. The main receptors transmitting signals from the ECM are members of the integrin family. However, although integrin-mediated cell-ECM anchorage has been long recognized as crucial for epithelial cell survival, the in vivo significance of this interaction remains to be weighed. In this work, we have used the Drosophila wing imaginal disc epithelium to analyse the importance of integrins as survival factors during epithelia morphogenesis. We show that reducing integrin expression in the wing disc induces caspase-dependent cell death and basal extrusion of the dead cells. In this case, anoikis is mediated by the activation of the JNK pathway, which in turn triggers expression of the proapoptotic protein Hid. In addition, our results strongly suggest that, during wing disc morphogenesis, the EGFR pathway protects cells undergoing cell shape changes upon ECM detachment from anoikis. Furthermore, we show that oncogenic activation of the EGFR/Ras pathway in integrin mutant cells rescues them from apoptosis while promoting their extrusion from the epithelium. Altogether, our results support the idea that integrins promote cell survival during normal tissue morphogenesis and prevent the extrusion of transformed cells.